Chronic Effects of Nicotine on Serum Lipid Profile and Oxidative Stress: An Experimental Study (Medical Forum Monthly, 2021)
Objective: To examine the chronic effect of nicotine on serum lipid profile and oxidative stress in male mice. Study Design: An Experimental Animal StudyPlace and Duration of Study: This study was conducted at the Department of Biochemistry, Liaquat College of Medicine & Dentistry, Karachi from February 2020 to April 2020 for a period of two months.Materials and Methods: Adult male BALB/C mice weighing 25-30 gm were housed in six cages under light and dark settings at 25oC and fed lab chow and water ad libitum under regular housing circumstances. Two sets of mice were created (control and test). There were 12 mice in each group. The drug-treated group received nicotine hydrogen tartrate (3.08 mg/ml) in 100 mL of drinking water for 28 days, whereas the control group got tap water.Results: After chronic nicotine delivery, there was a significant difference in glucose concentration, body weight, and plasma albumin concentration (P<0.01). Between the control and test groups, there was a significant difference in LDL-C and triglycerides (P<0.001). The levels of total cholesterol and HDL-C are unaltered. MDA levels in the liver (P<0.001), reduced glutathione and catalase activity (P<0.01), and brain MDA, reduced glutathione and catalase activity (P<0.01), (P<<0.001), and (P0.001), respectively, were all determined to be significant.Conclusion: In conclusion chronic administration of nicotine caused change in lipid profile, promoted lipid peroxidation and significantly reduced liver antioxidant enzyme activities in mice. It could be inferred that nicotine users have increased LDL-C and triglycerides which makes them more vulnerable to cardiovascular events.